The second Bush presidency global perspectives - Gupta, Amit 1958-; Samuel, Cherian (Pearson Longman, 2006)
Relations of the United States with India, China, and Europe, Canada, and South America.
Includes bibliographical references. - Online resource; title from title page (Safari, viewed January 23, 2015)
Keywords: Bush, George W -- 1946- -- (George Walker); Unilateral acts (International law); Bush, George W; (George Walker); 1946-; 2001-2009; Actes unilatéraux (Droit international); Diplomatic relations; Public opinion; États-Unis; Relations extérieures; 2001-2009; États-Unis; Opinion publique étrangère; United States; United States -- Foreign relations -- 2001-2009; United States -- Foreign public opinion